Risk of Transmission of Antimicrobial Resistant Escherichia coli from Commercial Broiler and Free-Range Retail Chicken in India - Hussain, Arif; Shaik, Sabiha; Ranjan, Amit; Nandanwar, Nishant; Tiwari, Sumeet K.; Majid, Mohammad; Baddam, Ramani; Qureshi, Insaf A.; Semmler, Torsten; Wieler, Lothar H.; Islam, Mohammad A.; Chakravortty, Dipshikha; et al. (Frontiers in Microbiology, 2017)
Multidrug-resistant Escherichia coli (E. coli) infections are a growing public health concern. This study analyzed the contamination of commercial poultry (broiler and free-range) with pathogenic and or multi-resistant E. coli in India. We analyzed 168 E. coli isolates from broiler and free-range retail poultry (meat/ceca) sampled over a wide geographical area, for their antimicrobial sensitivity, phylogenetic groups, virulence determinants and extended-spectrum-β-lactamase (ESBL) genotypes, fingerprinting by Enterobacterial Repetitive Intergenic Consensus (ERIC) PCR and genetic relatedness to human pathogenic E. coli using whole genome sequencing (WGS). The prevalence of ESBL producing E. coli between broiler and free-range chicken were: meat 44%; ceca 40% versus meat 15% and ceca 30%, respectively. E. coli from broiler and free-range chicken exhibited varied prevalence ranges for multi-drug resistance (meat 68%; ceca 64% and meat 8%; ceca 26%, respectively) and extraintestinal pathogenic E. coli (ExPEC) contamination (5% and 0%, respectively). WGS analysis confirmed two globally emergent human pathogenic lineages of E. coli- ST131 (H30-Rx subclone) and ST117 among these poultry E. coli. These results suggest that commercial poultry meat are not only an indirect public health threat by being carriers of non-pathogenic MDR-E. coli, but also poses a direct threat by acting as carriers of human E. coli pathotypes. Particularly, the free-range chicken represented low risks of contamination with antimicrobial resistant and extraintestinal pathogenic E. coli (ExPEC). Overall, these observations reinforce the zoonotic potential hypothesis linked to the food animal reservoir particularly the poultry.